Pro- and anti-angiogenic VEGF mRNAs in autoimmune thyroid diseases. (17th August 2016) - Rancier, Marc; Zaaber, Ines; Stathopoulou, Maria G.; Chatelin, Jérôme; Saleh, Abdelsalam; Marmouch, Héla; El Shamieh, Said; Masson, Christine; Murray, Helena; Lamont, John; Fitzgerald, Peter; Mahjoub, Silvia; et al.
Abstract: The aim of this study was to assess the relationships between five different splice isoforms of VEGF mRNA and its plasma levels in individuals treated for autoimmune thyroid diseases (AITD); mainly Graves' disease (GD) and Hashimoto's thyroiditis (HT). In a population from Tunisia, levels of thyroid hormones and antibodies were quantified simultaneously with plasma VEGF and VEGF mRNA isoforms after a period of 6 months of patients' treatment. Plasma VEGF was measured in 110 AITD patients (21 GD and 89 HT patients). VEGF isoforms (VEGF121, VEGF165, VEGF145 and VEGF189 pro-angiogenic isoforms and VEGF165b anti-angiogenic isoform) in peripheral blood mononuclear cells were quantified in 71 patients (20 GD and 51 HT patients) and 86 healthy controls. Decreased levels of VEGF189 mRNA were observed in AITD compared to controls. VEGF165 was increased in GD patients compared to controls and the VEGF165b was increased in HT patients compared to GD. We observed increased levels of VEGF165b in hypothyroid AITD patients after treatment. We have also shown that the VEGF145 isoform levels were determined by FT4 in all patients and by the thyroid status after 6 months of treatment only in HT patients. An association was observed for VEGF165 mRNA levels with anti-TPO antibodies in all patients. Finally, FT4 was associated with VEGF plasma levels but only in healthy controls. In conclusion, this descriptive study highlights the specificity of VEGF mRNA isoforms in AITD, a fact underlining the need for novel clinical trials and the development of personalised theranostic approaches.